Solution to Fractional Integro-differential Equation with Unknown Flux on the Dirichlet Boundary - article, In this; existence, we prove the; results., uniqueness; some stability results for fractional integro-differential equation of reconstruction of the unknown time-dependent boundary function from an additional integral measurement by the use of Rothe time discretization. Numerical experiments are given to illustrate the (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we prove the existence, uniqueness and some stability results for fractional integro-differential equation of reconstruction of the unknown time-dependent boundary function γ ( t) from an additional integral measurement θ ( t) =_Ω I^1-α ( u( t, x) ) dx by the use of Rothe time discretization. Numerical experiments are given to illustrate the results.